Pengaruh Aliran Kas Operasi, Laba Akrual, Tingkat Hutang, Dan Ukuran Perusahaan Terhadap Persistensi Laba Dengan Book Tax Differences Sebagai Variabel Pemoderasi - Novitasari, Cindy; Yanuar Rahmat Syah, Tantri (Fakultas Ekonomi Universitas Gresik, 2023)
This study aims to determine the effect of operating cash flow, accrual earnings, debt levels and company size on earnings persistence. In addition, to test whether the book tax differences variable can moderate the relationship between each independent variable on earnings persistence. The sample for this research is a manufacturing company with the consumer goods sub-sector listed on the IDX during the 2016-2020 period. The total sample is 15 companies using purposive sampling technique. Methods of data analysis using multiple linear regression with the help of the SPSS 23 program. The results showed that partially the cash flow variables, and company size have a significant positive effect on earnings persistence, accrual earnings variables have a significant negative effect on earnings persistence, and the level of debt has no significant effect on earnings persistence. Large positive (negative) book tax differences do not moderate the effect of operating cash flow, accrual earnings, debt levels and company size on earnings persistence.